Exploring the Educational Potential of AI Generative Art in 3D Design Fundamentals: A Case Study on Prompt Engineering and Creative Workflows (Global Journal of Human-Social Science, 2023)
AI will be increasingly integrated into artistic practices and creative workflows with prompt engineering assuming an increasingly important role in the process With readily-available generative AI such as Midjourney DALL-E 2 and Craiyon formerly DALLE-mini anyone can seemingly create art prompting questions about the future necessity of art and design education However whereas the ease with which content can be created has seen an outcry from the traditional artmaking community fears over widespread adoption replacing the need for a firm foundation in art and design principles and fundamentals is unfounded Instead these tools should be seen and adopted as other photomechanical and computer-generated versions before them and leveraged to provide new models for artists to improve their workflow Therefore the case study here proposed the use of AI generative art for a traditional 3D design studio art course to determine the manner and degree of process change that may be expected and to determine potential benefits of the new technology As such students were prompted to use the Craiyon or DALLE-2 art generator to gather verbal cues to combine three different objects into a new version that would then be realized as a physical three-dimensional sculpture and or model The assignment manifested in different ways including literally typing the three objects or providing adjectives Results indicate that proper prompt engineering including an interaction between objects resulted in positive outcomes However the study suggests that the principles of art and design will continue to be necessary and a module on prompt design and creation should be included in the curriculum This study can serve as a model for other art and design departments seeking to integrate AI into their courses through a pragmatic use case and example assignment